Women’s Perspective on the Surakarta Kebaya based on Biographies of Gusti Noeroel and Utami Suryadarma - Ira Adriati; Irma Damajanti; Almira Belinda Zainsjah (ITB Journal Publisher, LPPM ITB, 2018)
The kebaya is a national dress for Indonesian women. This paper analyzes the development of the Surakarta kebayas used by Gusti Noeroel, a princess who lived in Mangkunegara Palace, and Utami Suryadarma, the daughter of a high rank police officer from Surakarta. They were selected as the subject of this research because they used the kebaya consistently throughout their lives despite their interaction with modern culture. This study used a historical approach, especially on women’s position in Indonesian society and the development of Indonesian culture and kebaya design. The data were collected from various publications. Gusti Noeroel and Utami Suryadarma were educated noblewomen. They interacted with modern culture from various nations, while consistently using the kebaya as a characteristically Indonesian dress. The model they initially wore, the Surakarta kebaya, developed by changing the collar and the length and by applying a tighter fitting design. In addition, the material used changed according to the times. We can conclude that these princesses’ abilities to adjust the kebaya according to each era, made their kebaya designs always up to date.